Diiron(ii) pentacarbonyl complexes as CO-releasing molecules: their synthesis, characterization, CO-releasing behaviour and biocompatibility. Issue 2 (29th November 2018) - Xiao, Zhiyin; Jiang, Ran; Jin, Jing; Yang, Xiuqin; Xu, Binyu; Liu, Xiaoming; He, Yabing; He, Yi
Abstract : The diiron(ii ) complexes liberated CO in a variety of solvents and the CO-releasing pathway was solvent-dependent. In less polar solvents, the CO-release went through a triiron intermediate. Cytotoxicity of the complexes varied with the halide and the thiolate. Abstract : Four diiron(ii ) carbonyl complexes, [Fe2 (μ-SR)3 (CO)5 X] (X − = Br −, I − ; R = CH2 CH3, CH2 CH2 CH3 ) were facilely synthesized by reacting [Fe(CO)4 X2 ] with monothiolates. Their potential as carbon monoxide-releasing molecules (CORMs) was systematically investigated, revealing that their CO-releasing behaviour is highly solvent-dependent. Specifically, in dimethyl sulfoxide (DMSO), the CO-releasing kinetics were fast. Intermediates with a lower oxidation state might be involved in the reaction. By contrast, in less polar solvents such as methanol, acetonitrile and dichloromethane, intermediates featuring the triiron carbonyl cation, [Fe3 (μ-SCH2 CH3 )6 (CO)6 ] +, were isolated. The triiron intermediate underwent further decomposition to liberate CO. One of the iodo complexes was also examined for its CO-release in PBS solution when solubilised with DMSO in the presence of deoxy-Mb and the CO-release was found to be quantitative. Furthermore, kinetic analyses were performed and the CO-release in general obeyed a first-order kinetic model. Plausible CO-releasing pathways are proposed for the parent complexes and the triiron intermediate. Assessments in cytotoxicity indicated that the cytoxicity of the diiron(ii ) complexes varied with both the halide and thiolate and those bearing bromide and the thiolate with longer chains were more biocompatible.